The Role of Sport Psychology Services for Elite Sports Athletes The Case of Azerbaijan - Dilara Rafi; Narmin Ahmadova; Samir Khurshudov (Baltic Journal of Sport and Health Sciences, 2025)
This research paper explores the role of sport psychology services for athletes in Azerbaijan, and examines the factors shaping the current state of psychological support within the country’s sports industry. The study investigates the limited adoption of these services, highlighting key challenges such as the scarcity of skilled sports psychologists, a lack of awareness regarding the benefits of psychological support, and the social stigma associated with athletes seeking such assistance. These factors collectively hinder the development and effectiveness of sports psychology services in Azerbaijan. By addressing these issues, the research offers valuable insights for sports federations and organizations, aiming to promote the successful implementation of psychological support systems and enhance athletes’ performance and well-being. The findings highlight the importance of expanding access to qualified professionals, fostering awareness about the value of psychological support, and challenging societal norms that discourage athletes from seeking help. The paper concludes by advocating a comprehensive framework to integrate sports psychology services into Azerbaijan’s sports industry, thereby contributing to the overall development and success of its athletes.